[PP.26.24] THE COST-EFFECTIVENESS OF CONVENTIONAL AMBULATORY BLOOD PRESSURE MONITORING IN HYPERTENSIVES. (September 2017) - Liu, Y.; Liu, X.; Fan, Y.; Du, L.
Abstract : Objective: It is need to assess the cost-benefit for routine ambulatory blood pressure monitoring programme in patients with high blood pressure. Design and method: Total of 200 patients with hypertension were divided equally into two groups of casual blood pressure(CBP group) and conventional ambulatory blood pressure monitoring (ABPM group, diagnostic monitoring before treatment, evaluation of curative effect after treatment by ABPM), the differences of cost-benefit with the same therapeutic schedule for recent, half of a year and after 1 year were analyzed between two groups. The curative effect evaluation at half of a year and after 1 year should be used ambulatory blood pressure monitoring in two groups. Results: In our hospital, the cost for each time of ABPM is 96 yuan which is lower or equal to any fee of target organ evaluation or other risk factor mornitoring for blood, heart, kidney and brain; The cost of ABPM group was higher 96–288 yuan for each patient than CBP group; The curative effect at six months or after 1 year in ABPM group were better than CBP groups, and the difference of total cost is not obvious. Conclusions: Routine ambulatory blood pressure monitoring in patients with hypertension at least once each before and after treatment is feasible, and it is conducive to individualized treatment precisely or improve medical quality and effect of blood pressure controlling. The recent cost is slightly higher in ABPM group than CBP group, but the long-term effect is better and also there are no significant differences in cost. It is Suggested should be used with routinely ambulatory blood pressure monitoring in patients with hypertension.